PENGARUH PROMOSI JABATAN, GAYA KEPEMIMPINAN DAN LOYALITAS KERJA TERHADAP KINERJA KARYAWAN PADA PT TOBA AGRO MANDIRI HUMBANG HASUNDUTAN - Simangunsong, Elisabeth; Togatorop, Helen; Sagala, Roslinda (KUKIMA : Kumpulan Karya Ilmiah Manajemen, 2023)
This research aims to determine the effect of promotion, leadership style and work loyalty on employee performance at PT Toba Agro Mandiri Humbang Hasundutan. Data collection was carried out through questionnaires and documentation techniques. The research method used was quantitative, with 32 respondents. Data analysis in this study used SPSS version 25. The results of this study showed that the variables of job promotion, leadership style and work loyalty simultaneously had a positive and significant effect on employees at PT Toba Agro Mandiri Humbang Hasundutan. Partially, it shows that job promotion has a positive and significant effect on employee performance at PT Toba Agro Mandiri Humbang Hasundutan with a regression coefficient value of 0.502 and a significance value of 0.000<0.05 (smaller than the error tolerance value). Leadership style has a positive and significant effect on employee performance at PT Toba Agro Mandiri Humbang Hasundutan with a regression coefficient value of 0.224 and a significance value of 0.020<0.05 (smaller than the error tolerance value). Work loyalty has a positive and significant effect on employee performance at PT Toba Agro Mandiri Humbang Hasundutan with a regression coefficient value of 0.191 and a significance value of 0.039<0.05 (smaller than the error tolerance value)